The Influence of Brand Awareness & Brand Image on Brand Trust and Customer Loyalty - Prasetyo Wimar Eko Cahyono; M. Taufiq Noor Rokhman; Novita Rifaul Kirom (JURNAL ECONOMINA, 2026)
This study examines the influence of brand awareness and brand image on brand trust and customer loyalty in Ganesha Bospom Workshop in Malang at Ganesha Bengkel Bospom Malang. The research aims to analyze how brand awareness and brand image contribute to building brand trust and how brand trust affects customer loyalty in a local automotive service business. This study employs a quantitative explanatory research design. Data were collected through a structured questionnaire distributed to 74 loyal customers of Ganesha Bengkel Bospom Malang and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that brand awareness and brand image have a positive and significant effect on brand trust. Furthermore, brand trust has a positive and significant effect on customer loyalty and is proven to mediate the relationship between brand awareness and brand image on customer loyalty. These findings suggest that customer loyalty is not solely formed by brand perceptions, but is strongly influenced by the level of trust customers place in the brand. Practically, the findings provide important implications for service-based businesses, particularly in the automotive service industry, to focus on building brand awareness and brand image as a foundation for strengthening customer trust and achieving long-term customer loyalty